Pharmacological and Clinical Applications of Natriuretic Peptides: Accepted Knowledges or Changing Views? - Izzi Valerio; Chiurchiu Valerio; Baldini P. Morena (Current Pharmaceutical Analysis, 2007)
Natriuretic peptides (NPs) are endogenous low molecular weight peptides known for their hypotensive activities. Due to their ability to induce both natriuresis (Na+ secretion) and diuresis, in fact, these peptides can profoundly decrease the body haemodynamic load, an effect which represents a main goal for all therapies aiming at improving the health of those subjects affected by different forms of heart and kidney failure. Over the years, many evidences have been provided for the involvement of NPs in the control of different cardiovascular parameters both in physiological and pathological conditions. This has led many researchers to test the possible therapeutic effects of different NPs and the pharmacological industries to develop exogenous NPs forms with a higher activity. This review aims then at summarizing the current knowledge about the therapeutic and clinical applications of NPs, also considering “atypical” NPs and the problems yet to be solved.
Keywords: NPPB gene